Montagem auricular do sensor para índice bispectral: estudo clínico analítico de concordância à frontotemporal - Fernandes, Thyago Araujo (2023)
Favoring pharmacoeconomics and preventing perioperative complications, the evaluation of processed electroencephalograms has become popular as hypnosis titration tool. There are situations that difficult the usual application of electrodes, raising questions about the adoption of different assemblies. Some topographies were evaluated, demonstrating for several reasons limited equivalence with the conventional one. The investigation of the auricular assembly was idealized, better supported than others by observing the International 10-10 System, preserving the position of the 'explorer' electrode and allocating the 'reference' sensor in the ear lobe, as an option to nasion, both electrically neutral. It was designed as an observational study with general anesthesia for laparoscopic abdominal surgeries with total intravenous general technique with propofol and remifentanil. Thirty three patients of both genders and no history of neurological diseases were evaluated. There were a total of 3.521 minutes of monitoring and 299 paired measurements of BIS (bispectral index), SEF 95% (spectral edge frequency) and SR (suppression rate). Individually there was an average observation of 113,6 min (58-215) and 9 (7-13) numerical entries in specific time frames. The difference in BIS means between the assemblies ranged from 0.12 to 7.28 (1.97). Except for moment T1 (loss of response to verbal command), Bland-Altman (BA) analysis established agreement between the montages for all temporal fragments, with no statistically significant difference in BIS measurements (p>0.05). Also with exception to T1, BA determined accuracy (approximately zero systematic error) and precision to the method (low dispersion limits of agreement from the central metric). Approximately 86% of the difference of all BIS measurements obtained were within the recommended limit of ten units. Among seven individual moments evaluated, four had more than 90% of records within the referred range. When assessing a stricter demarcation - of five units - there were 55% of the measurements within the interval. Evaluating the surgical hypnosis maintenance period, a similar performance was observed: near zero systematic error (1.07); narrowly dispersed limits of agreement from de central metric (-13.02/15.16); about 90% and 60% of the measurements situated in the intervals of ±10 and ±5 units respectively. Pearson's analysis showed a moderate or strong positive correlation for most of the evaluated moments. As for SEF 95% parameter, there was a difference in the means measured by the assemblies, ranging from 0.39 to 0.91 (0.62), with no statistical significance in any of the time frames (p>0.05). There was positive SR in the auricular assembly more frequently from intubation moment to 30 minutes after surgery (p<0.05). Establishing a parallel between auricular and conventional assemblies, interchangeability was evidenced in the evaluation of BIS and SEF 95% for practically all perioperative time frames, the same was not verified for SR.